FEATURES OF TOURISM DEVELOPMENT UNDER CLIMATE CHANGE: SEASONALITY AND MINIMIZING ITS NEGATIVE IMPACT (Marketing Journal, 2025)
A common trend and simultaneously a serious problem in tourism is seasonality, characterized by sharp increases in tourist flows in the summer and declines in the winter and, especially, the autumn -spring months. Seasonality in tourism is influenced № 10-SON OKTA BR, 2025 -YIL 15 by both climatic and social factors. Climatic factors primarily stem from the fact that in most regions of the globe, weather conditions favorable for recreation and tourism vary from month to month, leading people to seek vacations during the most favorab le times of year.
Keywords: tourism; seasonality; climate; “off season”; tour